All Questions Topic List
None Questions
Previous in All Question Next in All Question
Previous in None Next in None
Question Number 204227 by abdomath last updated on 09/Feb/24
Answered by deleteduser1 last updated on 09/Feb/24
Lety=f(x)⇒x2y3=(x+y)5⇒x2[f(x)]3=(x+f(x))5⇒ddx(x2[f(x)]3)=ddx(x+f(x))5⇒3x2[f(x)]2f′(x)+2x[f(x)]3=5(x+f(x))4(1+f′(x))⇒f′(x)[3x2y2−5(x+y)4]=5(x+y)4−2xy3⇒dydx=5(x+y)4−2xy33x2y2−5(x+y)4
Answered by cortano12 last updated on 09/Feb/24
ddx(x2y3)=ddx(x+y)52xy3+3x2y2y′=5(x+y)4(1+y′)3x2y2y′−5(x+y)4y′=5(x+y)4−2xy3dydx=5(x+y)4−2xy33x2y2−5(x+y)4
Answered by Frix last updated on 09/Feb/24
2xy3dx+3x2y2dy=5(x+y)4dx+5(x+y)4dy(3x2y2−5(x+y)4)dy=(5(x+y)4−2xy3)dxdydx=5(x+y)4−2xy33x2y2−5(x+y)4
Terms of Service
Privacy Policy
Contact: info@tinkutara.com